2018
DOI: 10.1007/s11356-017-1132-6
|View full text |Cite
|
Sign up to set email alerts
|

Pollution and ecological risk assessment of nutrients associated with deposited sediments collected from roof and road surfaces

Abstract: Surface-deposited sediment in urban areas is an essential environmental medium for assessing nutrient contamination. The total nitrogen (TN) and total phosphorus (TP) pollution associated with surface-deposited sediments can be transported into urban water bodies by runoff and can cause eutrophication of those water bodies. By analyzing the samples collected on roof surfaces and road surfaces, this study provides a comparison of the differences in TN and TP pollution loading in sediments on these two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…They can carry many other dangerous pollutants, e.g. heavy metals or nutrients (Wang et al 2021 ; Wu et al 2018 ). The content of some pollutants increased in the Czechówka River after intense rainfall and snow melt (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…They can carry many other dangerous pollutants, e.g. heavy metals or nutrients (Wang et al 2021 ; Wu et al 2018 ). The content of some pollutants increased in the Czechówka River after intense rainfall and snow melt (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed previously, the sediments can be a source of contamination to the water column, predominantly Cd, Cr, Cu, Pb and Zn, particularly when they are attached to organic sediments [58]. Furthermore, Wu et al [67] reported that finer sediments, as formed by organic matter, tend to have higher metal concentrations and readily wash off into water bodies. This is of particular concern as the Geoaccumulation index (I geo ) revealed that Zn, Cu, Ti, and V are moderately contaminated in sediments and from the perspective of Pb, sediments are moderately contaminated to contaminated, particularly in the zone of the reservoir free of E. crassipes.…”
Section: Potential Toxic Metal In Sedimentsmentioning
confidence: 95%
“…During rainfall events, these particles are washed off and transported through urban drainage systems, becoming one of the most critical sources of non-point source pollution, causing water quality impairment in receiving water bodies, and are dominant stressors in urban aquatic ecosystems. 4–6…”
Section: Introductionmentioning
confidence: 99%
“…During rainfall events, these particles are washed off and transported through urban drainage systems, becoming one of the most critical sources of non-point source pollution, causing water quality impairment in receiving water bodies, and are dominant stressors in urban aquatic ecosystems. [4][5][6] Urban runoff is a critical vector of pollutants: it has been shown that they are contaminated by different chemical compounds that are transported mainly in the particulate phase and can vary considerably from one area to another. [7][8][9] Sediments act as indicators of environmental quality for stormwater because they can adsorb harmful pollutants such as nutrients, heavy metals, pesticides, and polycyclic aromatic hydrocarbons (PAHs) from the extensive and intensive impacts of anthropogenic activities.…”
Section: Introductionmentioning
confidence: 99%